ROLE OF BASAL AND PROVOCATIVE SERUM PROLACTIN IN DIFFERENTIATING IDIOPATHIC HYPOGONADOTROPIC HYPOGONADISM AND CONSTITUTIONAL DELAYED PUBERTY -A DIAGNOSTIC DILEMMA - Ali, Liaqat; Adeel, Afrose (Journal of Ayub Medical College Abbottabad, 2012)
Background: The prevalence of Idiopathic Hypogonadotropic Hypogonadism (IHH) is approximately 1 in 10,000 men. Objectives of this study were to evaluate the role of basal and stimulated serum prolactin in differentiating Constitutional Delayed Puberty (CDP) from IHH. Methods: This crosssectional study was carried out at the Department of Diabetes and Endocrinology, Military Hospital, Rawalpindi. A total of 20 male patients presenting with provisional diagnosis of IHH/CDP were enrolled in the study. Patients with known diseases were excluded from the study. Baseline FSH, LH, testosterone, and prolactin were estimated and the patients were subjected to provocative prolactin stimulation by Thyrotropin releasing hormone stimulation (TRH) test and chlorpromazine challenge. At each 6 monthly follow-up visit for 4 years, the patients were evaluated for adrenarche, pubarche and other secondary sexual characters. Tanner scale was taken as standards for comparing stage of puberty at a particular age. No treatment was given to both groups for 2 years. At the end of 2 years IHH patients with failed puberty or progression of puberty and CDP who lagged behind by more than 2 years by Tanner scale or 4 years per bone age with compelling psychosocial or psychosexual reasons at school or at home were given short courses of 50 mg injection testosterone in an attempt to expedite the onset or progression of puberty. Patients from either group with failed puberty after low dose testosterone were managed with high dose testosterone therapy to induce secondary sexual characters. Results: Twenty patients enrolled in the study were provisionally divided into 2 groups called IHH (n=9), and CDP (n=11) based on high basal and provocative serum prolactin levels in CDP group. Two patients from CDP group were lost in the follow-up leaving 9 patients in each group. A total of 10 (56%) patients, 3 (17%) from IHH group and 7 (39%) from CDP group achieved grade 4 puberty without any treatment. Remaining 8 (44%) patients, 6 (67%) from IHH group and 2 (22%) from CDP group were induced secondary sexual characters with full dose of 100 mg testosterone given parenterally at 4 weeks intervals. Conclusion: Differentiation between IHH and CDP on the basis of basal and post-TRH and Chorpromazine challenge reported earlier could not be substantiated by our study. Keywords: Hypogonadotropic hypogonadism, Constitutional delayed puberty, prolactin, FSH, LH